2020
DOI: 10.1038/s41598-020-58311-0
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Interaction with Immune Receptors is Modulated by Ripening Process in Papayas

Abstract: Dietary fibers have been shown to exert immune effects via interaction with pattern recognition receptors (pRR) such as toll-like receptors (tLR) and nucleotide-binding oligomerization domain (noD)like receptors. Pectin is a dietary fiber that interacts with PRR depending on its chemical structure. Papaya pectin retains different chemical structures at different ripening stages. How this influence PRR signaling is unknown. The aim of this work was to determine how ripening influences pectin structures and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…4 E). It has been shown previously that RGI-type pectins activated the canonical NF-κB pathway through various TLRs (mainly TLR2 and 4) and MyD88 ( Prado et al., 2020 ). Prado et al.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…4 E). It has been shown previously that RGI-type pectins activated the canonical NF-κB pathway through various TLRs (mainly TLR2 and 4) and MyD88 ( Prado et al., 2020 ). Prado et al.…”
Section: Resultsmentioning
confidence: 96%
“…It has been shown previously that RGI-type pectins activated the canonical NF-κB pathway through various TLRs (mainly TLR2 and 4) and MyD88 ( Prado et al., 2020 ). Prado et al. (2020) also showed that the lower molecular weight pectins were able to activate NF-κB through nucleotide-binding oligomerization domain-containing protein 2 (NOD2), and to a lesser extent, NOD1 in a dose dependent manner.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other receptors, such as complement receptor 3 (CR3), scavenger receptors (SRs), and nuclear oligomerization domain-2 (NOD-2), have been shown to bind to polysaccharides causing an immunostimulating response [ 9 , 65 , 90 , 91 ]. CR3, a member of the beta-integrins [ 92 ] is known to cause the activation of Syk, leading to the activation of phosphatidylinositol 3-kinase [ 93 ].…”
Section: Mechanisms Of Immunomodulation By Nag Polysaccharidesmentioning
confidence: 99%
“…Different scavenger receptors, such as SCARF1 and CD36, which bind to β-glucans, have also been shown to work in conjunction with TLR2 [ 103 , 104 , 105 ]. NOD-2 is a member of the NOD—leucine rich repeat (LRR), or NOD-like receptor (NLR) family of receptors, which is known to bind peptidoglycans and can be activated by muramyl dipeptide, but has also been shown to bind partially digested polysaccharides [ 90 , 106 , 107 ]. NOD-2 then signals to RIP-2 (also known as RICK), which leads to the IKK activation through TAK1 signaling [ 107 , 108 ].…”
Section: Mechanisms Of Immunomodulation By Nag Polysaccharidesmentioning
confidence: 99%